Assessment of Lifestyle Behaviors of Nursing Students During the COVID-19 Pandemic - Şeyma Nur Hepokur Yıldırım; Yeter Kitiş (Hemşirelikte Araştırma Geliştirme Dergisi)

(untitled)
Objective: The objective of this study is to evaluate the changes in lifestyle-related behaviors of nursing students in the fourteenth and fifteenth months of the COVID-19 pandemic. Methods: This research was conducted in descriptive type. 489 nursing students studying at 25 universities randomly selected, stratified by region and proportionally, participated in the research. Data were collected using the sociodemographic characteristics questionnaire and the Lifestyle Behavior Questionnaire. Data were analyzed using Kolmogorov-Smirnov, Mann-Whitney U, Kruskal Wallis-H, Mann-Whitney U with Bonferroni correction and Pearson chi-square tests.Results: The results showed that participants adopted healthier diets and struggled with stress and anxiety. Female participants adopted healthier diets, received more social support, and participated in physical activities more often but experienced more anxiety and stress than their male counterparts. Fourth-year students ate less junk food and experienced less anxiety and stress than first- and second-year students. Participants in big cities adopted more unhealthy diets than those in small towns. Participants who had tested positive for COVID adopted healthier diets than those who had not (p